Anterior Mitral Leaflet Translocation during Correction of Combined Mitral-Aortic Valve Disease - V. V. Popov; O. O. Bolshak; V. J. Boukarim; R. M. Vitovskiy; Y. V. Bakhovska (Ukrainian Journal of Cardiovascular Surgery, 2020)
The aim. To study the possibilities of techniques for preserving left ventricular (LV) contractility during mitral valve replacement (MVR) and correction of combined mitral-aortic valve disease (CMAVD). The analyzed group included 257 patients with CMAVD who were undergoing surgical treatment at the Institute. In 97 patients, MVR was performed with translocation of the chordae of the anterior leaflet muscles in combination with complete preservation of the posterior leaflet. Of the 97 operated patients, 2 (2.1%) died at the hospital stage (within 30 days after the operation). Inotropic support (dobutamine) ranged from 3 to 4 ¤g/min/kg during the first 48 hours. The patients were discharged on average 9-12 days after surgery without clinically significant complications. There were no complications at the hospital stage associated with the operative technique. In significant dilation of the left ventricle, MVR with an option of maximizing the preservation of the chordo-papillary continuum is an essential procedure.Materials and methods. The analyzed group included 257 patients with CMAVD who were undergoing surgical treatment at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine from January 01, 2006 to January 01, 2020. In addition to MVR, all the patients underwent aortic valve replacement with a mechanical prosthesis. The patients had left ventriculomegaly with an end-diastolic volume exceeding 300.0 ml. In 97 patients, MVR was performed with translocation of the chordae of the anterior leaflet with simultaneous complete preservation of the posterior leaflet of the mitral valve (main group A). The remaining 160 patients underwent MVR without preserving the subvalvular chordopapillary continuum (comparison group B).Results. Among 97 operated patients of the group A, 2 died (2.1%) at the hospital stage (within 30 days after the operation). The dynamics of echocardiographic indicators within 10-11 days of the postoperative period was as follows: LV end-systolic index (ml/sq.m) was 88.4 ± 11.1 (before surgery), 69.4 ± 8.2 (after surgery) and 49.4 ± 7.2 (long-term period); left ventricular ejection fraction (LVEF) was 0.52 ± 0.03 (before surgery), 0.55 ± 0.03 (after surgery) and 0.57 ± 0.03 (long-term period); left atrium (LA) diameter was 62.2 ± 4.5 mm (before surgery), 49.5 ± 1.7 mm (after surgery) and 50.5 ± 1.5 mm (long-term period). Diastolic gradient of a mitral prosthesis was 13.2 ± 2.4 mm Hg. In the long-term period, the mean follow-up of the patients was 8.2 ± 2.4 years.In group B, among 160 operated patients, 5 (3.1%) died at the hospital stage. The dynamics of echocardiographic indicators within 10-11 days of the postoperative period was as follows: LV end-systolic index ( ml/sq.m) was 89.4 ± 11.5 (before surgery), 76.4 ± 9.2 (after surgery) and 62.4 ± 7.2 (long-term period); LVEF was 0.52 ± 0.03 (before surgery), 0.54 ± 0.03 (after surgery) and 0.55 ± 0.03 (long-term period ); LA diameter (uncorrected) was 63.2 ± 3.5 mm (before surgery), 60.5 ± 1.7 mm (after surgery) and 64.5 ± 2.7 mm (long-term period). Diastolic gradient of a mitral prosthesis was 12.7 ± 2.4 mm Hg.Conclusions. Based on the obtained clinical experience, it seems appropriate to recommend the original operation of translocation of the anterior mitral valve leaflet for the correction of combined mitral-aortic defects.